(untitled) (Italian Journal of Public Health, 2006)
The National Health Service in England has focused on improving cancer services over the last decade, following indications from the international EUROCARE study that cancer services, and survival, were behind other comparable countries. New managerial structures and processes have been created to encourage service specialization by cancer type, develop coordination between hospitals and improve access times for patients. However, within the NHS in England as a whole, the government has been encouraging market ideas that contrast with this centralist direction. To improve patient ‘choice’, an improved information system, drawing on timely clinical and administrative data, is needed for cancer care commissioning.